Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan PT. Adaro Energy Tbk Periode 2021-2023 - Mustofa Adin; Roy Irawan (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to analyze the financial performance of PT. Adaro Energy Tbk for the period 2021-2023 using the Index Time Series method. PT. Adaro Energy Tbk is an integrated energy company that focuses on coal mining. The data analyzed comes from the company's financial statements published on the Indonesia Stock Exchange. The research method is quantitative non-statistical with a purposive sampling technique to determine the sample. Data analysis techniques include Time Series calculations by looking at the financial performance values of the Liquidity, Solvency, and Profitability Ratios. The results of the analysis show that the financial performance of PT. Adaro Energy Tbk In the period 2021-2023, the company's Current Ratio increased from 2.08% in 2021 to 2.17% in 2022, before decreasing slightly to 2.01% in 2023. Despite the decline, the company still has sufficient liquidity. Debt to Equity Ratio dropped significantly from 83.47% in 2021 to 41.33% in 2023, signaling the end of management in reducing debt. Profitability through Net Profit Margin (NPM) increased from 23.27% in 2021 to 30.75% in 2022, but decreased to 25.22% in 2023. The results of this study provide stakeholders with insight into the dynamics of the company's financial performance, as well as provide a good foundation for making financial decisions in the future.